Snow Road Construction Technique by Layered Compaction of Snowblower Processed Snow. - Thomas,M. W.; Vaudrey,K. D. (1973)
Elevated high-strength snow roads are constructed over the deep snowfields in Antarctica between McMurdo Station and the Williams Field complex to move cargo and personnel in rubber-tired vehicles. The purpose of this experiment was to simplify the existing techniques developed by the Naval Civil Engineering Laboratory (NCEL) for constructing these snow roads. To achieve this objective, new cutter-heads were installed on the ski-mounted snowblower, the pulverized snow was deposited and spread in 4-inch layers which were compacted by walking the area with LGP D-8 tractors. This modified procedure is described as it was performed in the field, followed by a recommended outline for future snow road construction. This new method eliminates the special ski-mounted snow mixers, a savings of both costly equipment and construction time. Tests results show that the experimental snow road densities and shear strengths compare favorably with those of previous roads, built by pulvimixing. The experimental test section held up under two months of wheeled traffic, proving that snow roads built by the new construction technique will give satisfactory service. (Author)